'I hope one more flower will bloom in my life': retelling the stories of being homeless in Japan through narrative inquiry. Issue 1 (2nd January 2019) - Kubota, Hiroko; Clandinin, D. Jean; Caine, Vera
ABSTRACT: Once becoming homeless, people confront various challenges. Despite hardships in their lives, the voices of people who are homeless are often silenced in society and the multiplicity of their experiences are undermined. To recognize the impact of homelessness from their understandings of life, the study reports in-depth conversations with people who are homeless in Japan. Through the qualitative research methodology of narrative inquiry, I engaged in a close relationship with three men who are/were homeless and inquired into their experiences of being homeless. From our conversations, four narrative threads emerged; (1) living with memories of loss, (2) feeling of being without control, (3) feeling discouraged from weaving forward-looking stories, and (4) nourishing generosity amidst unexpected life circumstances. Considering these narrative threads, we highlight the diversity in the experiences of becoming/being homeless in Japan embodied by the stories of three men. We put forward recommendations for future practice and knowledge development to support people who are homeless.